Nutritional ergogenics and sports performance (1998)
The purpose of this review is to provide a broad overview of selected individual nutrients and dietary supplements purported to possess ergogenic properties. Space does not permit a detailed analysis of all specific studies, so most of the references cited are either principal studies or review papers that may provide the interested reader with more detail.